PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 038 SEKELADI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Rina Rina; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The problem this research is the students achievement of Science studies SD N 038 Sekeladi fourth graderes still low with an average value of 60,00 and minimum completenness criteria (KKM) Science studiesis 65. Between students, amounting to 20 people only 8 students who achieve classical KKM with 40,00%. This research is classroom action research (CAR), which aims to improve the student achievement of Science studies class IV at SD N 038 Sekeladi with implementation cooperative learning model type Think Pair Share (TPS). Formulation of the problem : is the implementation of cooperative learning model type Think Pair Share (TPS) can improve students achievement of Science studies at SDN 038 Sekeadi. The research was conducted on Mart, 2016 ‘to Juny, 2016 by 2 cycles. Subjects werw students of SDN 038 Sekeladi, totaling 20 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action an improve in base score cycle with the average being 60,00. In the first cycle improve an average of 76,20 and an improve in the second with an average 87,60. Activities of the teacher in the learning process in cycle of 57,14% and the second meeting improve to 64,28%. In the third cycle of the first meeting and the second meeting improveKey Words: Cooperative Learning Model Type Think Pair Share (TPS), Achievement of Science